Morphological and DNA Sequence Data of Two New Millipede Species of the Thyropygus induratus Subgroup (Diplopoda: Spirostreptida: Harpagophoridae) - Pimvichai, Piyatida; Enghoff, Henrik; Backeljau, Thierry (Tropical Natural History, 2023)
The common cylindrical millipede genus Thyropygus (family Harpagophoridae) comprises four informal species groups, one of which is the T. allevatus group. This group is characterized by two synapomorphic gonopodal characters: (1) gonopods with tibial and femoral spines and (2) the tibial spine is very long and recurved proximad towards the femoral spine. The T. allevatus group is further divided into four subgroups: (1) T. allevatus subgroup, (2) T. opinatus subgroup, (3) T. induratus subgroup, and (4) T. cuisinieri subgroup. Based on gonopodal characters and COI barcoding, two new species of the T. induratus subgroup are described from Loei Province, Thailand, viz. T. panhai sp. nov. and T. somsaki sp. nov. The small uncate subterminal lobe (a hook-like process) at the basal part of the palette of the telopodite is the synapomorphy that assigns these two new species to the T. induratus subgroup. The two species are morphologically also well-differentiated from each other. In contrast, the COI data neither provide strong support for their placement in the T. induratus subgroup, nor provide strong support for their species level differentiation, since their interspecific COI divergence of 7% is at the borderline between the intraspecific divergences in T. induratus, T. uncinatus and T. resimus (5–6%, but with values of up to 12%) and the mean interspecific divergence within the T. induratus subgroup (12%; range: 7–15%). Hence, the taxonomic interpretation of T. panhai sp. nov. and T. somsaki sp. nov. as separate species within the T. induratus subgroup is, for the time being, almost entirely based on morphology.